C3 Promotes Clearance of Klebsiella pneumoniae by A549 Epithelial Cells - de Astorza, Beatriz (American Society for Microbiology, 2004)
The airway epithelium represents a primary site for contact between microbes and their hosts. To assess the role of complement in this event, we studied the interaction between the A549 cell line derived from human alveolar epithelial cells and a major nosocomial pathogen, Klebsiella pneumoniae, in the presence of serum. In vitro, we found that C3 opsonization of poorly encapsulated K. pneumoniae clinical isolates and an unencapsulated mutant enhanced dramatically bacterial internalization by A549 epithelial cells compared to highly encapsulated clinical isolates. Local complement components (either present in the human bronchoalveolar lavage or produced by A549 epithelial cells) were sufficient to opsonize K. pneumoniae. CD46 could competitively inhibit the internalization of K. pneumoniae by the epithelial cells, suggesting that CD46 is a receptor for the binding of complement-opsonized K. pneumoniae to these cells. We observed that poorly encapsulated strains appeared into the alveolar epithelial cells in vivo but that (by contrast) they were completely avirulent in a mouse model of pneumonia compared to the highly encapsulated strains. Our results show that bacterial opsonization by complement enhances the internalization of the avirulent microorganisms by nonphagocytic cells such as A549 epithelial cells and allows an efficient innate defense.